2019
DOI: 10.1111/ced.13964
|View full text |Cite
|
Sign up to set email alerts
|

Novel nonsense mutation of the SLC39A4 gene in a family with atypical acrodermatitis enteropathica

Abstract: Click https://www.wileyhealthlearning.com/ced.aspx for the corresponding questions to this CME article.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 4 publications
0
6
0
Order By: Relevance
“…However, it has been reported that some patients with AE presented only with a typical skin rash and a normal level of serum zinc. The reason may be that they had been taking an oral zinc supplement intermittently or that one of the SLC39A4 alleles in the compound heterozygous mutation barely affected the transport of zinc (9,15). So far, more than 52 mutations have been reported in patients with AE, including missense mutations, nonsense mutations, frameshift mutations, splice site mutations, and so on (16).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, it has been reported that some patients with AE presented only with a typical skin rash and a normal level of serum zinc. The reason may be that they had been taking an oral zinc supplement intermittently or that one of the SLC39A4 alleles in the compound heterozygous mutation barely affected the transport of zinc (9,15). So far, more than 52 mutations have been reported in patients with AE, including missense mutations, nonsense mutations, frameshift mutations, splice site mutations, and so on (16).…”
Section: Discussionmentioning
confidence: 99%
“…The clinical symptoms of AE usually appear within several weeks or months after birth, with the highest incidence around weaning age, and they vary with age ( 9 , 10 ). AE is characterized by periorificial dermatitis, alopecia, and diarrhea.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1,2 Alopecia has been described as a component of the classic clinical triad of AE along with dermatitis and diarrhea. 2,4 Case reports have referred to observable scalp hair abnormalities in AE as diffuse hair thinning (or sparse hair), 3,[5][6][7][8][9][10][11] brittle or fragile hair, 12,13 hair loss, 10,14-16 and universal nonscarring (or total) alopecia. 4,[17][18][19][20][21][22][23][24][25] In addition, structural hair shaft changes on light and polarized microscopy have been documented, including variations in hair diameter with a spindle-shaped appearance, 12 atypical trichorrhexis nodosa with stretch fractures and kinking, 12 pseudo-monilethrix nodal swellings, 12,26 cortex thinning, 3 and irregular pattern of alternating dark and bright bands.…”
Section: Discussionmentioning
confidence: 99%
“…2,4 Case reports have referred to observable scalp hair abnormalities in AE as diffuse hair thinning (or sparse hair), 3,[5][6][7][8][9][10][11] brittle or fragile hair, 12,13 hair loss, 10,14-16 and universal nonscarring (or total) alopecia. 4,[17][18][19][20][21][22][23][24][25] In addition, structural hair shaft changes on light and polarized microscopy have been documented, including variations in hair diameter with a spindle-shaped appearance, 12 atypical trichorrhexis nodosa with stretch fractures and kinking, 12 pseudo-monilethrix nodal swellings, 12,26 cortex thinning, 3 and irregular pattern of alternating dark and bright bands. 3,12 Zinc deficiency was shown to interfere with hair follicle cycling, 27,28 keratinization, 29 and immune homeostasis in murine models, [29][30][31] though little is known about its role in human hair disorders.…”
Section: Discussionmentioning
confidence: 99%